INVESTIGATION OF ACTIVATED CARBON CHARACTERISTICS IN POLYETHYLENE TEREPHTHALATE PLASTIC WASTE - Irhamni Irhamni; Atika Ruhayyah; T Muhammad Ashari (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2023)
Abstract: TPA is the final location of the urban waste processing process by hoarding waste in landfills. The decomposition of waste and exposure to rainwater in landfills will produce a concentrated liquid, leachate. The presence of heavy metals at certain concentrations will turn toxic to aquatic ecosystems. In addition, high COD levels indicate the presence of large amounts of organic pollutants. One alternative to removing these contaminants is by using the adsorption method. In particular, this study aimed to determine the characteristics of activated carbon and the best dose variation in reducing pollutants in leachate. The analysis results of the characteristics of activated carbon in PET plastic waste are 2.2% moisture content, 2.6% ash content, 62.2% volatile matter content, and 33% bound carbon content. The water and ash content values complied with SNI 06-3730-1995, but for volatile matter content and bound carbon content, they did not comply with SNI 06-3730-1995. The best dose in reducing levels of heavy metals Fe and COD was at a 15-gram dose with a final value of Fe of 0.106 mg/L with an efficiency of 96.4% and COD of 3404 mg/L with an efficiency of 36.7%. Overall, the Fe metal content for all cases tested met the RI Minister of Health Regulation Number 32 of 2017. However, the COD level had not yet reached the quality standard of the Minister of Environment and Forestry Regulation Number 59 of 2016. Keywords: Adsorption, polyethylene terephthalate and characteristics.